Large-Scale Multi-omic Analysis of COVID-19 Severity - Overmyer, Katherine A.; Shishkova, Evgenia; Miller, Ian J.; Balnis, Joseph; Bernstein, Matthew N.; Peters-Clarke, Trenton M.; Meyer, Jesse G.; Quan, Qiuwen; Muehlbauer, Laura K.; Trujillo, Edna A.; He, Yuchen; Chopra, Amit; et al. (Cell systems, 2021)
We performed RNA-seq and high-resolution mass spectrometry on 128 blood samples from COVID-19-positive and COVID-19-negative patients with diverse disease severities and outcomes. Quantified transcripts, proteins, metabolites, and lipids were associated with clinical outcomes in a curated relational database, uniquely enabling systems analysis and cross-ome correlations to molecules and patient prognoses. We mapped 219 molecular features with high significance to COVID-19 status and severity, many of which were involved in complement activation, dysregulated lipid transport, and neutrophil activation. We identified sets of covarying molecules, e.g., protein gelsolin and metabolite citrate or plasmalogens and apolipoproteins, offering pathophysiological insights and therapeutic suggestions. The observed dysregulation of platelet function, blood coagulation, acute phase response, and endotheliopathy further illuminated the unique COVID-19 phenotype. We present a web-based tool (covid-omics.app) enabling interactive exploration of our compendium and illustrate its utility through a machine learning approach for prediction of COVID-19 severity. [Display omitted] •We surveyed biomolecules in 102 COVID-19 and 26 non-COVID-19 patient blood samples•We found 219 biomolecules strongly associated with COVID-19 status and severity•We observed pronounced dysregulation of lipid transport and neutrophil degranulation•Our resource of measurements and patient data is located at https://covid-omics.app Leukocyte mRNA expression and plasma protein, metabolite, and lipid levels were measured in 102 COVID-19 and 26 non-COVID-19 patient samples. 219 diverse biomolecules were strongly associated with COVID-19 status and severity and pointed to dysregulation of processes related to lipid transport, blood coagulation, acute phase response, endotheliopathy, and neutrophil degranulation in this disease.